Implantation of trifocal intraocular lens in mild pathologic myopia: visual outcomes and influence of fundus structures - Meiyi Zhu; Zongsheng Zeng; Wei Fan; Guangbin Zhang (BMC Ophthalmology)
Abstract Purpose To compare the visual outcomes of simple high myopia (HM) and mild pathologic myopia (PM) following implantation of a trifocal intraocular lens (IOL), and investigate the influence of fundus structures. Methods We retrospectively studied 63 high myopic eyes of 63 patients underwent femtosecond laser-assisted cataract surgery with implantation of AT LISA tri 839MP IOL (Carl Zeiss Meditec AG, Germany) between July 2020 and September 2024. 34 eyes in the HM group and 29 eyes in the PM group. Main visual outcomes including monocular corrected distance (4 m, CDVA), distance-corrected intermediate (80 cm, DCIVA), distance-corrected near (40 cm, DCNVA) visual acuity, defocus curves, and subjective refraction. Optical coherence tomograph was employed to evaluate macular tilt degree (MTD), central foveal thickness, and subfoveal choroidal thickness. Multiple linear regression analysis was used to evaluate the independent predictors of visual acuity in the PM group. Results The CDVA, DCIVA, and DCNVA were 0.00 ± 0.00, 0.08 ± 0.05, and 0.09 ± 0.07 logarithm of the minimum angle of resolution (logMAR) in the HM group, 0.02 ± 0.05, 0.15 ± 0.09, and 0.17 ± 0.09 logMAR in the PM group, respectively. In the PM group, mean MTD was 17.13 ± 6.79°. The MTD demonstrated a significant predictive effect on CDVA (regression coefficient: 0.005; P = 0.026) and DCNVA (regression coefficient: 0.015; P = 0.003). Conclusion Trifocal IOL implantation yielded favorable visual outcomes in simple high myopic eyes, though results were comparatively poorer in PM cases. MTD was associated with the expected visual outcomes.